Role of Sufism in Spreading Shiism at Kermanshah - Dadfar, Sajjad; Radeh, Ghobad (Journal of History Culture and Art Research, 2017)
Abstract Researchers, whether Muslim or not, refer to Sufism as limbo between Sunni and Shia beliefs with an emphasis on its weak Sunni and strong Shia ties. History and expand of Shia in Kermanshah support this statement also. Kermanshah is one of the regions that provided a proper social environment for Shia to strengthen its presence due to Sufi movements and dignitaries. Meanwhile, in addition to strengthen convergence areas of Shi’ism and Sufism, some events such as the Mongol onslaught and efforts of strong figures in Sufism exacerbated conditions to spread Shiism in the region. The present research aims to examine the role of Sufism in spreading Shiism in Kermanshah, in addition to investigate areas of the convergence.